Stereo Sensors-based Object Segmentation and Location for a Bin Picking Adept SCARA Robot - Hema, Chengalvarayan Radhakrishnamurthy; Paulraj, Murugesapandian; Ramachandran, Nagarajan; Sazali, Yaacob (Universiti Malaysia Perlis, 2010)
Link to publisher's homepage at http://jere.unimap.edu.my